2015
DOI: 10.3997/2214-4609.201412839
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Analysis of Finite-element Schemes for a First-order Formulation of the Wave Equation

Abstract: SUMMARYWe investigated one-dimensional numerical dispersion curves and error behaviour of four finite-element schemes with polynomial basis functions: the standard elements with equidistant nodes, the LegendreGauss-Lobatto points, the Chebyshev-Gauss-Lobatto nodes without a weighting function and with. Mass lumping, required for efficiency reasons and enabling explicit time stepping, may adversely affect the numerical error. We show that in some cases, the accuracy can be improved by applying one iteration on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Since inversion of this large sparse matrix is costly, mass lumping can be applied, but then the superior dispersion behaviour is lost. For that reason, Shamasundar et al (2015) proposed the use of defect correction as an efficient alternative. In 1D, we found that one iteration with the consistent mass matrix, preconditioned by the mass-lumped mass matrix, reduced the numerical dispersion error.…”
Section: Introductionmentioning
confidence: 99%
“…Since inversion of this large sparse matrix is costly, mass lumping can be applied, but then the superior dispersion behaviour is lost. For that reason, Shamasundar et al (2015) proposed the use of defect correction as an efficient alternative. In 1D, we found that one iteration with the consistent mass matrix, preconditioned by the mass-lumped mass matrix, reduced the numerical dispersion error.…”
Section: Introductionmentioning
confidence: 99%